A new, nearly complete stem turtle from the Jurassic of South America with implications for turtle evolution - Sterli, Juliana (2008)
Turtles are known since the Upper Triassic (210 million years old) however fossils recording the first steps of turtle evolution are scarce and often fragmentary. As a consequence, the main discussion nowadays is if living turtles (Testudines) originated during the Late Triassic (210 myo) or during the Middle to Late Jurassic (~160 myo). The discovery of the new fossil turtle (Condorchelys antiqua gen. et sp. nov.) from the Middle to Upper Jurassic (~160-146 myo) of South America (Patagonia, Argentina) presented here sheds new light on early turtle evolution. An updated cladistic analysis of turtles shows that C. antiqua and other fossil turtles are not crown turtles, but are stem turtles. This cladistic analysis also shows that stem turtles were more diverse than previously thought and that until the Middle to Upper Jurassic there were turtles without the modern jaw closure mechanism.